O método EDABO para determinação da umidade da castanha-do-brasil (Bertholletia excelsa H.B.K.) - Monteiro, Luciano de Magalhães (2015)
For proper handling of a product knowledge regarding its moisture content is essential. To provide fast, inexpensive and reliable results, the direct evaporation method of water in oil bath (EDABO) has been proven to be a viable alternative, at all stages of production of the Brazil nut. Therefore, adaptation and validation of the EDABO method for the almonds was developed using ten lots, five for each stage, maintaining the moisture range between 3.73 and 29.13% w.b, which is the typical moisture range for the product from the collection phase until its final marketing. The oil bath temperatures tested were 150° C to 200° C, from 10 to 10° C for the adaptation step. The results thus obtained were compared with the moisture content recorded for the same batch employing the vacuum oven method as the standard. In the adaptation step the most suitable temperature range was set. Next, the method was validated to test for the precision, accuracy and linearity of the pre-set temperature range. During this step, temperature of 150° C were observed to ensured moisture results consistent with those determined by the standard method. In the validation step the temperature of 150° C revealed precision, accuracy and linearity and were comparable to the standard method. Therefore, considering the technical aspects for implementation of this method, it was concluded that 150° C temperature was validated